Pemahaman Terhadap Quarter Life Crisis Yang Terjadi Dimasa Perkembangan Dewasa Awal: Suatu Kajian Literatur - Bagus Hafarinto; Selly Rahmayati; Salsabila Laurensia; Delvina Faulin; Alrefi Alrefi; Minarsi Minarsi (Scidacplus, 2024)
Identity finding and personal fulfillment adding another layer to the Quarter Life Crisis. The attempt to find ‘myself’ is inextricably linked to societal expectations, family dynamics, and the constant comparisons that occur through social media. As a person to define their values, beliefs, and passions, they often struggle with fear of making the wrong choices and deviating from social norms. Robinson (2020) emphasizes that a Quarter Life Crisis is often a time in which individuals reflect on life values, search for meaning, and evaluate whether the path they have chosen is consistent with their identity. This research aims to gain deeper insight into the impact of QLC on Indonesia's young generation and how they can address the challenges that arose during this period. As well as identifying factors that influence QLC in early adult students in Indonesia. In this study, the researchers used a literature study method. The researchers have been searched the literatures from journal articles related to the Quarter-life crisis (QLC) in early adulthood from 2019-2023. The factors that could trigger new problems in this phase include lack of confidence in one's own abilities, negative perceptions of oneself and the influence of social media which results in the emergence of comparing behavior between self-achievements and others’ achievements. Quarter-life crisis is a crisis situation commonly experienced by young people in early adulthood, including students in Indonesia. Quarter life crisis is characterized by over-worry, pessimism, anxiety, and even depression. The triggers of a quarter-life crisis are diverse and include difficulty on finding a job that matches your passions, difficulty of making decisions, fears, and rapid change.